The Teachers’ Efficacy In Employing Teaching Tools To Teach Arabic At the South Eastern University Of Sri Lanka/ فعالية المعلمين في توظيف الوسائل التعليمية لتعليم اللغة العربية في جامعة جنوب شرق سريلانكا - Fathima Sabrina Abdul Azeez (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Arabic is considered one of the most important languages in the world. It is the language of the Holy Quran and the language of Islamic civilization. It is also a living language that constantly evolves and renews itself. The teacher is the cornerstone of teaching this language and transmitting it to successive generations. The teacher plays a pivotal role in guiding students toward learning Arabic and acquiring its various skills. To achieve this, the teacher relies on a diverse range of educational tools that help deliver information effectively and engagingly. Evaluating the effectiveness of these educational tools in achieving learning objectives is crucial, as it contributes to developing teaching methods and improving learning outcomes. Hence, this research aims to evaluate the effectiveness of using teaching tools in improving students' proficiency in various Arabic language skills (reading, writing, listening, and speaking) at the South Eastern University of Sri Lanka. The research employs a descriptive-analytical approach, utilizing a closed-ended questionnaire administered to both students and teachers. Data analysis is then conducted using the Statistical Package for the Social Sciences (SPSS). The results reveal that the use of teaching tools led to a significant improvement in students' proficiency across all language skills, particularly reading and writing. These findings indicate that the use of teaching tools in the South Eastern University of Sri Lanka is an effective method in teaching Arabic, and it is recommended that teachers be trained in their effective use and integrated into the curriculum.